The role of master's degree programme in strategic development of higher educational institution - I. . Kim; S. . Lisienko (Moscow Polytechnic University, 2022)
An efficient development of competency-based educational process requires lecturers with high scientific and innovative potential. In order to increase considerably such competencesof senior lecturers and teaching assistants Far Eastern State Technical Fisheries University implements Master's programme for their training, which provides a noticeable increase in academic potential as well as creation of methodically self-developing environment at theacademic department while lecturers-candidates for Master's degree are working on their pedagogical theses.